Fortifying Nuclear Security: Cultivating Vigilance Culture Among Personnel for Enhanced Prevention and Response - Sabariah Kader Ibrahim; Sonia Naz (International Journal of Nuclear Security, 2025)
A vigorous nuclear security culture is crucial in preventing the theft and sabotage of nuclear material. It requires vigilance from all employees because relying solely on closed-circuit television systems and security personnel is insufficient to deter potential threats. Employee attentiveness plays a vital role in recognizing and preventing suspicious activities. However, achieving a strong security culture is challenging because of the lack of incidents in some facilities, leading to employee complacency. This paper highlights the pivotal role of personnel in the success of nuclear security measures, emphasizing the need for a proactive and vigilant mindset among staff. Through the analysis of case studies and real-world incidents, this study explored the effect of an enhanced vigilance culture on incident detection, response times, and overall security protocol effectiveness. The study delved into psychological and organizational factors influencing vigilance culture development, emphasizing leadership commitment, continuous training, and a sense of shared responsibility among security personnel. The proposed framework for promoting vigilance culture integrates practical strategies, including scenario-based training, regular debriefings, and leveraging technological advancements such as artificial intelligence for improved threat detection. Contributing to the nuclear security discourse, this paper provides insights into the tangible benefits of a vigilance culture within nuclear facilities. The findings offer practical recommendations for security managers, policymakers, and training professionals to fortify security culture and mitigate potential risks in the ever-evolving landscape of nuclear security.
Keywords: Nuclear Security Culture; Vigilance Culture; Scenario-based Training